Monitoring Temperature and Humidity of Boiler Chicken Cages Based on Internet of Things (IoT) - Dhimas Dwiki Sanjaya; Abdul Fadlil (Universitas Ahmad Dahlan, 2023)
Animal husbandry is a business sector that is growing rapidly. Poultry is very popular with the community, especially broiler chickens. However, breeders find it difficult to maintain the condition of broiler chickens because these poultry are heat stress birds that are easily stressed if the coop conditions are too hot or cold. Because of this, this research was conducted to design a system that can control the temperature and humidity values of the chicken coop automatically. The system designed in this study uses a DHT11 sensor which is useful for detecting the temperature and humidity values of the chicken coop. The microcontroller used is NodeMCU. The temperature and humidity values are sent via IoT (Internet of Things) to the ThingSpeak media platform. The fan will turn on if the temperature value is more than 31Â° C. The mist maker will light up if the humidity value is less than 55%, and the incandescent lamp will light up if the temperature value is less than 29Â° C. The system testing performed resulted in a temperature error value of 1,05% and humidity error value of 2,39%. The system's ability to turn on fans, mist makers, and incandescent lamps when the temperature value does not match the conditions can also run well.